Effect of Zn addition on the corrosion behaviours of as-cast BCC Mg-11Li based alloys in NaCl solution - Chuanqiang Li; Binbin Deng; Linjie Dong; Binqing Shi; Yong Dong; Feng Peng; Zhengrong Zhang (Materials & Design, 2022)
Effect of Zn on the corrosion behaviours of Mg-11Li-xZn (x = 0, 1, 3, 6; termed as L11, LZ111, LZ113, LZ116) alloys in 0.1 M NaCl solution has been investigated. The results reveal that corrosion resistance of four alloys increases following the order LZ116 < LZ113 ≈ L11 < LZ111. Besides, filiform-like corrosion occurs at early corrosion stage for the four alloys, while additional pitting corrosion preferentially emerges in the L11, LZ113 and LZ116 alloys with immersion time. The small alloying Zn can reduce corrosion rate of Mg-11Li alloys, and excess Zn will accelerate the corrosion due to the existence of micro-galvanic effect between second phase and matrix. Regarding of the surface film, double layers of considerable thick outer layer and inner layer can be observed on the top of L11 and LZ111. Nevertheless, small alloying Zn is prone to modify the surface film and contributes to the high corrosion resistance of LZ111 alloy, while high Zn concentration results in the rapid corrosion damage of surface films on the LZ113 and LZ116 alloys and further elevate corrosion rate.